Study of the electron densities of some food products dried using the new method - Nuroglu, Emine; Bursalioglu, Ertugrul O.; Karabul, Yasar; Bakirdere, Sezgin; Icelli, Orhan (TAYLOR & FRANCIS INC, 2016)
The main goal of this study was to determine the concentrations of P, S, Cl, K, Ca, and Sr in food samples using a newly developed drying method to find their electron densities. The methods applied to samples to find the effective drying method were as follows: drying in oven under a magnetic field and drying under the sun and a magnetic field. Concentrations of elements were determined by an energy dispersive X-ray fluorescence spectrometer soon after initial processing of dried foods. The concentrations of elements were acquired as mg/kg. An attempt was made to calculate the electron densities of the dried samples. The electron densities of food samples dried in oven under a magnetic field as the effective one were identified using ZXCOM software. This particular attempt is fairly new, and there is no information in this field. The electron density (N-eff) values of the dried samples were calculated for all samples of interest. The electron densities of fig samples dried with the new method suggested in this study were found to be highest among all samples of interest.
Keywords: Dried food; drying process; EDXRF; electron density; magnetic field; EFFECTIVE ATOMIC-NUMBER; TRACE-ELEMENTS; SYNCHROTRON-RADIATION; BORON-COMPOUNDS; COMPTON RATIO; TISSUES; RAYLEIGH; COPPER; INDUSTRY; PROGRAM; Engineering